Diversity and seasonal changes of zooplankton communities in the Shatt Al-Arab River, Basrah, Iraq, with a special reference to Cladocera - Abbas, M.F.; Salman, S.D.; Al-Mayahy, S.H. (Mesopotamian Journal of Marine Sciences, 2022)
Zooplankton abundance and distribution were studied at four stations in the northern sector of Shatt Al-Arab from September 2008 to August 2009. Monthly zooplankton samples were collected.Oblique hauls were taken at each stationusing a 0.120 mm mesh-sized net with 40 cm mouth opening. Air and water temperatures, salinity, pH, dissolved oxygen, turbidity, chlorophyll-a, total suspended solids and total soluble solids were measured at each station and at each sampling event and were correlated with the density of Cladocera. Like Shannon index, Jaccardʼs similarity index,measures of richness and evenness were calculated. Water temperature ranged from 10 to 28 ºC. Salinity values changed from 0.7 to 4.1 psu with a decline in the summer and an increase in the autumn. pH values were >7, dissolved oxygen varied from 4.9 in the summer to 12.3 mg/l in the winter. Chlorophyll-a values fluctuated between 2.3 in the autumn and winter and 21.4 mg/m3 in Summer.Zooplankton density was the least at station 1 (79-10074 ind/m3) and the most at station 2 (174-65170 ind/m3).Cirripede larvae dominated the zooplankton community at all the stations. Cladocera was second in number, followed by Copepoda.The maximum diversity index (2.11), richness (64.45) and evenness (0.47) were obtained at station 1. The highest similarity was obtained between stations 3 and 4 and the lowest between stations 1 and 2.